Antimicrobial activity of naphthalene lysine conjugated peptide hydrogels. Issue Volume 1(2019)Issue A (8th March 2019) - Afami, Marina Ellie; Karim, Ikhlas El; Laverty, Garry; Lundy, Fionnuala
Abstract : The synthesis of hydrogel scaffolds with inherent antimicrobial activity has advantages for their use in tissue engineering. An ultra-short naphthalene lysine conjugated peptide, NapFFK'K', containing naphthalene (Nap) as a molecule of high aromaticity for gel strength, phenylalanine (F) and epsilon variant lysine (K') has previously been shown by us to self-assemble forming hydrogels with inherent antimicrobial properties against a limited number of pathogens tested. The aim of this work was to extend the antimicrobial activity studies on NapFFK'K' including pathogenic bacteria associated with dental infections. NapFFK'K' was synthesised using the 9-fluorenylmethoxucarbonyl Solid Phase Peptide Synthesis. Peptide purity was analysed by mass spectrometry. Hydrogel formulation was achieved by suspending the peptide in sterile deionized water followed by addition of NaOH and HCl. Hydrogels were tested at peptide concentrations of 1 %, 1.5 % and 2 % w/v against the Gram-positive bacteria Enterococcus faecalis and Staphylococcus aureus, and the Gram-negative bacterium Fusobacterium nucleatum . Bacteria inoculumns were exposed on hydrogel surface for 24 h. Bacterial susceptibility assay, employing the Miles and Misra method, was used to determine antimicrobial activity of hydrogels after 24 h incubation. Our results show that peptide hydrogels exhibit antimicrobial properties against both groups of bacteria but at different peptide concentrations. The 1 % peptide hydrogels was most effective against Gram-positive bacteria whereas the 2 % peptide hydrogel was effective against Fusobacterium nucleatum . Given the efficacy of the self-assembling NapFFK'K' peptide hydrogels against oral pathogens, they may have potential use in tissue engineering approaches for regenerative endodontic treatments.